1981
DOI: 10.1111/j.1365-2133.1981.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding studies on suspensions of isolated epidermal keratinocytes

Abstract: The sugar composition of the surface of isolated human keratinocytes has been investigated using lectins. A method is described in which the FITC-labelled lectin is displaced with competing sugar prior to measurement. This avoids errors due to aspecific binding and utilizes the minimum biological sample. Evidence is presented which indicates that little cell surface glycoconjugate is lost during the preparation of the keratinocyte suspension from human epidermal slices using the technique described here. Value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The findings correlated with the pattern in whole adult mouse skin (Table i) where the various antigens are characteristic of progressively more differentiated cells (Brabec et ai, 1980;Nemanic & Elias, 1979;Brysk & Snider, 1982). Thus, irrespective of other characteristics of primary mouse epidermal cell cultures, the cell surface glycoconjugates seem to be similar to those occurring in whole epidermis, just as the cell surface glycoconjugates of human primary cell suspensions (Gommans & van den Hurk, 1981) were similar to those in whole human epidermis (Gommans & van den Hurk, 1982). Arrest or delay of differentiation by either retinoids or calcium deprivation prevented or greatly diminished the orderly appearance of A'-acetyl-galactosamine, fucose, and iV-acetyl-glucosaminc on the cell surface.…”
Section: Discussionsupporting
confidence: 75%
“…The findings correlated with the pattern in whole adult mouse skin (Table i) where the various antigens are characteristic of progressively more differentiated cells (Brabec et ai, 1980;Nemanic & Elias, 1979;Brysk & Snider, 1982). Thus, irrespective of other characteristics of primary mouse epidermal cell cultures, the cell surface glycoconjugates seem to be similar to those occurring in whole epidermis, just as the cell surface glycoconjugates of human primary cell suspensions (Gommans & van den Hurk, 1981) were similar to those in whole human epidermis (Gommans & van den Hurk, 1982). Arrest or delay of differentiation by either retinoids or calcium deprivation prevented or greatly diminished the orderly appearance of A'-acetyl-galactosamine, fucose, and iV-acetyl-glucosaminc on the cell surface.…”
Section: Discussionsupporting
confidence: 75%
“…The sources of the chemicals used in this investigation have been detailed in a previous publication (Gommans & van den Hurk, 1981). The protein content of each batch of FITC-labelled lectin was determined by measurement of optical densities at 278 nm and 492 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately the difficulties in isolating pure plasma membrane fractions coupled with the very limited amount of tissue available from human biopsy makes this approach impractical. However, lectins (specific sugar-binding proteins) can be used as sensitive and reliable tools for the study of cell-surface sugars (Sharon & Lis, 1975), and the application ofthis technique to normal human epidermis has recently been described (Gommans & van den Hurk, 1981). In the present paper we report the extension of this work to keratinocytes derived from psoriatic lesions and the uninvolved epidermis of psoriatic patients.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…It is well known that lectins obtained from plants and animal origins link specifically to sugar residues in cells; thus, lectin-binding can be used as a histochemical technique for the demonstration of cell saccharide residues. Tissues and cells of animals contain carbohydrates in their surface coats, in intercellular materials interposed between epithelial cells, and in secretory components of glands and they also show positive reaction with lectins which have been conjugated to fluorescein isothiocyanate (FITC) or horseradish peroxidase (HRP) (6,10,23,25). In histochemical studies using lectins on stratified squamous epithelium, Stegman et al (28) (25) and Hosaka et al (10) have reported that the cell surface, intercellular gaps, and basement membrane of epithelial cells contain specific sugar residues such as Gal, GalNAc and G1cNAc under the normal condition, however, these residues are reduced markedly in amount in the malignant state (11).…”
mentioning
confidence: 99%